Tiktok, gen z symbiotic network for augmented reality and immersive advergaming - Martín Ramallal, Pablo (2021)
The incessant changes in the modes of interrelation arising from ICT (Information and Communication Technologies) bring avant-garde ways of communicating, especially among the new generations. Social networks seem to have become the agora of postmodernity and any discourse that aspires to consolidate itself must adapt to them. Mixed realities (MRe), exemplified by virtual reality (VR) and augmented reality (AR) do not escape this axiomatic truth. The main networks natively integrate AR filters as layers of enriched information. Advertisers, eager to reach an elusive audience, have realized its storytelling potential. The objective is to test the compatibility of AR as a resource for advertising campaigns in RRSS supported by advergames with a transmedia strategy. The methodology is based on a triangulation whose vertices comprise a case study, a discourse analysis and a focus group (FG). The results derive from the analysis of two emblematic actions embedded in TikTok, a social network of exponential growth among the generation z. The campaigns under review are “WeStart” by Ma French Bank's and “You're On” by Ray Ban's. A series of reflections are brought to discussion regarding the advantages and peculiarities of integrating these strategies as an advertising story. As general conclusions, generation z seems to be called to adopt immersion as something proper to their social modes and cybercultural iconography, including this premise to transmedia advertising. In addition, AR advergames in social media find in transmedia a catalyst to reach their maximum performance.